Daily returns seasonality and impact of stock index futures: evidence from the Kuala Lumpur Stock Exchange - Mohamad, Azhar; Bacha, Obiyathulla Ismath; Ibrahim, Mansor (KLSE and RIIAM, 2003)
This paper examines the impact of Stock Index Futures (SIF) trading on Day of Week (DOW) pattern of daily Kuala Lumpur Stock Exchange returns. We address a total of four research questions using both a simple OLS model and a GARCH (1,1) specification. Three daily return measures, CTC, OTC, CTO are used. The impact of DOW pattern on the new T+3 day settlement is also examined.